PENGEMBANGAN JAWA BARAT SEBAGAI PROVINSI JASA - Ria Satyarini (Bina Ekonomi, 2009)
Jawa Barat as the next province after DKI Jakarta has many strategic roles. Jawa Barat has a vision to be the most advance province  in 2012, according  to the vision Jawa Barat has to achieve that vision and reach the opportunity. There are so much  to do and big challenges that Jawa Barat has  to deal with. But  the important things is how  the government recognize classification  of services and knows the challenge they  face.